THE PROBLEMS FACED BY STUDENTS IN LEARNING ENGLISH SPEAKING SKILLS AT ENGLISH EDUCATION DEPARTMENT UNIVERSITAS MUHAMMADIYAH YOGYAKARTA BATCH 2012 - Andreas Corsini Giri Sinta (PBI 15 UMY 020)
*20 peaking skill is one of important skills in learning language. Many students both Indonesian and other countries face problems in learning English speaking skills. The students are expected to solve the problems in order to get better speaking skills. This study aims to identify the problems faced by students in learning English speaking skills and to investigate the students’ strategies in learning English speaking skills. This study uses the quantitative approach and takes survey design. This study was conducted at English Education Department Universitas Muhammadiyah Yogyakarta. The population was all of the students of EED UMY batch 2012 and the population number of this study was 114 participants. The sample of this study was 98 participants. The sample was taken using convenience sampling. To gather the data, the researcher utilized questionnaires and the data were analyzed in descriptive statistic. The findings shows that students possesses several problems in learning English speaking skills. The problem are that most students face inhibition, nothing to say, low participation, mother tongue use, lack of motivation, lack of vocabulary, lack of grammar, and lack of pronunciation. The findings also reveal some students’ strategies in learning English speaking skills as follows: technical means, practice alone, using of question clarification, communication with native and non-native speaker, self-monitor, self-evaluation, and repetition. In short, this study reveals that almost all of students of EED UMY batch 2012 encounter the problems in learning English speaking skills.